2009
DOI: 10.4067/s0717-97072009000300010
|View full text |Cite
|
Sign up to set email alerts
|

The Ball Milling Effect on Tribasic Calcium Phosphate and Its Chromium (Vi) Ion Sorption Properties

Abstract: The ball milling effect on the sorption properties of tribasic calcium phosphate (TCP) is presented. The materials obtained were characterized by X-ray diffraction, SEM, particle size and specific surface area. The specific surface area of the prepared TCP prepared sample was 60.55 m 2 /g and unexpectedly decreased to 12.57 m 2 /g for samples where milling time was 15 hrs. In TCP samples with a milling time of 5 and 10 h, the specific surface values also diminished to 16.81 and 15.11 m 2 /g, respectively. Fe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…However, the obtained values show the contrary in the case of the PBM process. This phenomenon was already observed by Granados-Correa et al [34] in their study on the ball milling effect on tribasic calcium phosphate powders. The explanation offered by Granados-Correa et al…”
Section: Ha-filled Suspension Preparationsupporting
confidence: 73%
See 1 more Smart Citation
“…However, the obtained values show the contrary in the case of the PBM process. This phenomenon was already observed by Granados-Correa et al [34] in their study on the ball milling effect on tribasic calcium phosphate powders. The explanation offered by Granados-Correa et al…”
Section: Ha-filled Suspension Preparationsupporting
confidence: 73%
“…The application of a lower energetic milling process as PBM produces a less intense particle size reduction of the HAInitial powder (x50 of 12 µm (measured in aqueous suspension)) [34]. As result, the PSD of the HAPBM powder becomes more disperse with two particles populations, one of 20 µm and another one of 2.5 µm.…”
Section: Ha-filled Suspension Preparationmentioning
confidence: 99%
“…At equilibrium, the retention of Cr(VI) on the adsorbent was found to be 7.10 × 10 -3 mmol/g at the surveyed pH 5.5. On the other hand, for the milled tri-calcium phosphate the corresponding value reported by Granados-Correa et al [10] was 7.5 × 10 -5 mmol/g. The higher equilibrium retention of chromate ions on Fe-mPO 4 proves that the increase in the amount of Fe deposited in calcium phosphate enhances the uptake of chromate ions.…”
Section: Effect Of Contact Timementioning
confidence: 62%
“…Various methods are available to remove chromium from wastewater and well established methods are reverse osmosis, ion exchange, electro-dialysis, coagulation, solvent extraction, adsorption and some others. In the case of adsorption process, many materials such as activated carbon [1][2][3], calcium alignate beads [4,5], biological wastes [6][7][8], Fe-modified pozzolane [9], tri-calcium phosphate [10], hydrotalcite [11] and others materials have been used for the removal of Cr(VI). Granados et al [10] studied the ball milling effect on tri-basic calcium phosphate (TCP) and its chromium (VI) ion sorption properties and they found that chromium (VI) sorption on milled TCP samples increased, unexpectedly, as the specific area became smaller.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Metal phosphates possessing remarkably large internal surface areas and narrow pore size distributions have attracted considerable attention for their great potential application as catalysts, adsorbents, and host materials. Recently, much work has been devoted to the metal phosphate materials synthesis, [7][8][9][10] and iron phosphate with porous structure would be interesting in terms of structure and adsorbent performance. Thus, the study of Cr(VI) retention on iron phosphate materials is helpful and essential for the evaluation of heavy metal physic-chemical behavior in the aqueous pollutant retention field.…”
Section: Introductionmentioning
confidence: 99%